GROWING TOO FAST: A CASE OF TESTOTOXICOSIS - Hui, Saw Shi; Giok, Lim Poi; Idris, Arini Nuran Binti Md (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Testotoxicosis is a rare cause of gonadotropin-independent precocious puberty in males due to an activating mutation in the luteinizing hormone (LH) ) /choriogonadotropin receptor (LHCGR) gene. This disorder usually presents at 2-4 years old with virilization, advanced bone age, and increased serum testosterone levels above adult ranges, despite low LH and FSH levels. CASE A 3-year 2-month-old male presented with complaints of acne, pubic hair, phallic growth, height accelerations, and behavioural issues. His parents were non-consanguineous and had no family history of precocious puberty. On physical examination, his height was 106cm (+2.36 SDS) and weight was 16 kg (+0.77 SDS). He had a muscular body build, a deep voice, and acne. He had Tanner stage 2 pubic hair, stretched penile length was 6 cm (>2 SDS), and both testicular volumes were 5 mls. He did not have café au lait spots. Bone age was 7 years old. Testosterone level was high at 17 nmol/L and gonadotropin-releasing hormone (GnRH) stimulation test revealed a prepubertal response (peak LH 1.44 u/L and FSH 3.02 u/L). Thyroid function tests (FT4: 13.77 pmol/L; TSH: 1.71 m IU/L) and adrenal hormone levels (DHEAS: 0.46 umol/L; 17-OHP: 3.42 nmol/L; cortisol: 400 nmol/L) were within normal ranges. Synacthen test excluded virilising congenital adrenal hyperplasia. Low serum beta-hCG (1.2 mIU/ml) excluded beta-hCG-secreting tumour. Testicular ultrasound showed no sonographic evidence of testicular lesion. Whole exome sequencing identified a heterozygous pathogenic variant c.169A>G (p.Asp564Gly) in LHCGR gene which supports the diagnosis of testotoxicosis. The child was started on aromatase inhibitor, Anastrozole 1mg daily, and anti-androgen, spironolactone 2 mg/kg BD. At 6 months of treatment, there was a halt in pubertal progression with reduced height velocity from 9 cm/year to 6 cm/year. CONCLUSION There was no consensus on the management of this rare condition. Without intervention, the patient will have rapid progressive skeletal maturation and virilization which will result in compromised adult height and psychosocial distress.